LIGHT-ROASTED GREEN COFFEE EXTRACT IMPROVED ADIPONECTIN, INSULIN RESISTANCE, AND METABOLIC PROFILE OF METABOLIC SYNDROME RAT MODEL - Lukitasari, Mifetika; Nugroho, Dwi Adi; Rohman, Mohammad Saifur; Nugrahini, Nur Ida Panca; Sardjono, Teguh Wahyu (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of this study is to investigate the effect of light-roasted green coffee bean extract (GCE) administration for 7 weeks on the improvement of metabolic profile, adiponectin level, homeostatic model assessment insulin resistance (HOMA-IR) index in metabolic syndrome (MS) rat model. Methods: Adult male Sprague-Dawley rats were induced by a combination of high sucrose and high-fat diet for 8 weeks and streptozotocin injection in the 2nd week. The MS was confirmed by NCEP-ATP III criteria. They were divided into six weight-matched groups (n=5), normal control, MS, metformin and simvastatin-treated group (DMS), 100 and 200/body weight (bw) GCE (GCE 100 and GCE 200, respectively). The extracts were given through oral gavage daily for 7 weeks. The effect of GCE on body weight, serum glucose, triglyceride, (TG) and high-density lipoprotein (HDL) level was analyzed by colorimetric method. HOMA-IR index and adiponectin were analyzed by enzyme-linked immunosorbent assay methods. Result: Fasting blood glucose, TG, and systolic blood pressure decreased significantly (p<0.05) in both GCE groups. Moreover, after 7 weeks, those parameters were significantly lower (p<0.05) compared to that of MS group. Only GCE 100 group that showed a significant decrease in HDL level. GCE 100 mg/bw and 200 mg/bw group showed significantly higher adiponectin level compared to that of MS and DMS group. Furthermore, GCE 100, GCE 200, and DMS group showed a significant lower HOMA-IR index compared to that of MS group. Conclusion: 7 weeks GCE administration could decrease fasting blood glucose, profile lipid, blood pressure, and improved adiponectin level and HOMA-IR index.